THE IMPACT OF GREEN FINANCE, ENVIRONMENTAL PERFORMANCE, INFLATION, AND ACTIVITY RATIOS ON FIRM VALUE: EVIDENCE FROM THE INDONESIA STOCK EXCHANGE. - Yuda Ramadan; Husaini; Nurhasanah; Jummaini (Journal of Accounting Research, Utility Finance and Digital Assets, 2026)
This study aims to analyze the effect of green finance, environmental performance, inflation, and activity ratios on firm value. The population of this study consists of 84 food and beverage companies. The sampling method used in this study is purposive sampling, resulting in a sample of 15 food and beverage companies listed on the Indonesia Stock Exchange during the period 2019–2023. This study employs secondary data obtained from the annual financial statements of the companies. The data analysis method uses a panel data regression approach processed using EViews 12 software. The results of this study indicate that partially, green finance, inflation, and total asset turnover do not have a significant effect on firm value. However, environmental performance has a positive and significant effect on firm value. Simultaneously, green finance, environmental performance, inflation, and total asset turnover do not have a significant effect on firm value.